619 Prospective Evaluation of anti-SSA/Ro Positive Pregnancies to Address Risk Factors for Fetal Cardiac Disease/Adverse Pregnancy Outcomes and Efficacy of Ambulatory Fetal Heart Rate Monitoring (FHRM) and Rapid Treatment of Emergent Block. (14th December 2022) - Buyon, Jill; Deonaraine, Kristina; Carlucci, Philip; Masson, Mala; Fraser, Nicola; Phoon, Colin; Roman, Ashley; Izmirly, Peter; Saxena, Amit; Belmont, Michael; Penfield, Christina; Lee, Young Mi; et al.
Abstract : Introduction: Fetal cardiac disease is strongly associated with maternal anti-SSA/Ro antibodies, but gaps in our knowledge include the influence of antibody specificity and titer, maternal diagnosis, overall non-cardiac adverse pregnancy outcomes (APOs), optimal surveillance protocols, and efficacy of rapid treatment. Methods: The multi-center S urveillance and T reatment To P revent Fetal AV B lock L ikely to O ccur Q uickly (STOP BLOQ) study recruited pregnant women with commercially positive anti- Ro antibodies and stratified them into high and low titers of anti-Ro60 and Ro52 based on a research ELISA, using a cutoff defined by that obtained for 50 mothers with previous AVB offspring. Mothers with anti-Ro60 and/or 52 antibodies at or above 1, 000 I.U. were trained to perform FHRM. From 17- 25 weeks of gestation, FHRM was completed 3x/day in addition to weekly or biweekly fetal echocardiograms (echo). Mothers texted all audio sounds to the coordinating center. Texts deemed abnormal by mothers were immediately sent to an on call pediatric cardiologist who either reassured if FHRM was normal or referred for emergency fetal echo in < 6 hours if abnormal. Results: 250 anti-Ro pregnant women (22% Hispanic, 50% white, 12% Black, 12% Asian, 4% other) have been consented, including 28 whose previous child had AVB. Of mothers tested to date, 153 were provided home monitors given high titer anti-Ro60 and/or 52 antibodies (26 high titer anti-Ro60 alone, 21 high titer anti-Ro52 alone, 105 high titer antibodies to both antigens). The 83 patients with low titers were surveilled with echos per local standard of care. Regarding maternal diagnosis, of 161 assessed to date, 39% were asym/UAS, 11% RA, 31% SS, 19% SLE. Antibody titers did not significantly differ by ethnicity, race or diagnosis (table 1). Non- AVB APOs occurred in 18% and were not predicted by Ro60 or 52 titers but rather SLE diagnosis (table 2). In total, 24, 759 FHRM audiotexts were received from 131 patients (90 of whom have delivered) during the monitoring period. Of these, 22 were evaluated by the on-call pediatric cardiologist, who prompted an emergency echo (all completed in < 6 hrs). In 11 cases, the emergency echo was normal. In 9, there were premature atrial contractions, confirming the mother's perception. In 2 with 2° block on urgent echo (both treated per protocol with IVIG and dexamethasone), 1 reverted to normal sinus rhythm and the other progressed to 3° block. In 2 others, the mother did not perceive abnormal FHRM for > 24 hrs, echo identified 3° block, and retrospective cardiology review of FHRM audio captures identified an abnormality prior to obtaining the echo. All 4 AVB developed in fetuses of mothers with high titer antibodies to both Ro60 and 52 (mean 32, 451 and 34, 991 respectively). Of the 18 mothers with a previous AVB child who followed the 400mg hydroxychloroquine PATCH protocol, 1 developed AVB in accord with the results of Step 1 in that study. Conclusion: These data support that APOs in this clinically diverse group of mothers are not influenced by anti-Ro titer or specificity, but rather SLE diagnosis. All conduction defects were initially identified by FHRM and in mothers with high titer anti-Ro60 and 52. Hydroxychloroquine continues to show efficacy in reducing the AVB recurrence rate with rapid intervention of emergent block being promising.